WRESTLING INJURIES DURING THE 2016 RIO OLYMPIC GAMES. Issue 4 (1st February 2017) - Shadgan, Babak; Molnar, Szabolcs; Sikmic, Stevan; Chahi, Abdelghani
Abstract : Background: Better understanding of the incidence, characteristics, predisposing factors and mechanisms of injuries in each sport helps to implement more effective preventive measures to better care for the athletes. Objective: The purpose of this study was to assess the injury profile of elite senior wrestlers in men's Greco-Roman, men's freestyle, and women's freestyle wrestling during the 2016 Rio Olympic Games. Design: Descriptive epidemiologic study. Setting: Clinical. Participants: 352 senior qualified wrestlers participated in 2016 Rio Olympic Games. Interventions: A web-based injury database system developed by UWW was used to collect the injury data during all wrestling competitions of the Games. Main Outcome Measurements: Included athlete's demographic, weight category, injury type, severity, location, timing, and mechanism. Results: A total of 352 athletes sustained 22 injuries during 410 matches, which is equivalent to an overall incidence of 6.2 injuries per 100 athletes (7.1% in men; 4.4% in women; P=0.31) and 5.4 injuries per 100 matches. Among the three styles, women's freestyle had the lowest injury rate (22.7%); men's freestyle and men's Greco-Roman sustained an injury rate of 36.4% and 40.9% respectively. More injuries were observed in the middleweight categories. The most common injury type was skin laceration and contusion (54.5%) due to direct contact, and the most common site of injury was forehead (36.4%). In sum, 54.5% of all injuries were categorized as light, 27.3% as mild and 18.2% as severe. Four bouts were terminated due to an injury. Conclusions: No serious and catastrophic injury was recorded during wrestling competitions of 2016 Olympic Games, and most injuries were minor. The rate of wrestling injuries during 2016 Rio Games (6.2% per athlete) were lower than 2012 London (12%) and 2008 Beijing (9.3%) Olympic Games. Higher education, improvements in wrestling regulations and more attention to wrestler's health care during recent years might explain this difference.